Connecting a city to the sea : the history of the Athenian long walls - Conwell, David H. (Mnemosyne, Supplements, 2008)
The Long Walls joining Athens with its harbors are universally recognized as symbols of naval imperialism and the lynchpin of a radical departure from traditional Greek military strategy during the later fifth century B.C. Nevertheless, many important questions about the structures remain disputed or simply neglected. As the first comprehensive history of the Long Walls, the present study dates each construction phase, examines the function of the structures from beginning to end, and chronicles their fluctuating viability. The analysis is driven by the proposition that the Athenians would not have relied on the walls to the sea when their navy did not control the sea lanes effectively. This full consideration of the Long Walls' development and strategic prominence over time will enable accurate assessment of their position in Greek military and political history from classical through early Hellenistic times.